Conservation Agriculture Enhances Soil Fauna Richness and Abundance in Low Input Systems: Examples From Kenya - Ayuke, Fredrick Ouma; Kihara, Job; Ayaga, George; Micheni, Alfred N. (Frontiers in Environmental Science, 2019)
Conservation agriculture (CA) is believed to improve soil nutrient status, soil structure, control soil erosion, and also enhance soil biodiversity. Despite the widespread interest in CA, empirical evidence of the benefits of CA on soil biodiversity is limited, especially in low-input systems of sub-Saharan Africa (SSA). Consequently, the magnitude and effect by CA on soil fauna remains unquantified. The aim of this study was to evaluate the effect of CA and associated management practices on soil fauna richness and abundance. We hypothesized that CA (zero tillage + organic inputs as surface residue) and mixed cropping would positively influence soil fauna richness and abundance. We compared CA with conventional till (CT; with or without residues) in sole maize and maize-bean cropping systems. Soil macrofauna and mesofauna were sampled across the treatments in medium-term (6 yrs) trials in Embu, Central Kenya, and Kakamega (6 yrs) and a long-term trial in Nyabeda (15 yrs) using soil monoliths and core samplers, respectively. In agreement with our hypothesis, higher macrofauna taxonomic richness and mesofauna was recorded in CA than in CT without residues. This study demonstrated that: 1) medium to long-term addition of organic residues enhances soil fauna richness and abundance, 2) CA increases soil fauna taxonomic richness and abundance compared with CT, and 3) CA under maize-bean intercropping, rotation and sole maize cropping systems promote soil fauna richness and abundance compared with sole legume (common beans). We conclude that adoption of CA is important in enhancing richness of soil fauna. Given the numerous challenges faced by smallholder farmers of SSA in the adoption of CA, who in most cases rarely practice all the three CA principles simultaneously, we propose a further study that will determine the effects and interactions between each of the CA components on soil fauna richness and abundance.